Ab initio investigations of electronic structure, optical transparency, and elastic properties in X3Al2Si3O12 (X = Ca, Mg). Issue 17 (1st December 2017) - Tu, Bingtian; Wang, Hao; Wang, Weimin; Fu, Zhengyi
Abstract: A series of ab initio simulations were performed to investigate the electronic, transparent, and elastic properties of Ca3 Al2 Si3 O12 and Mg3 Al2 Si3 O12 which have potential applications in lithography optics, lenses and phosphor materials. From the simulated electronic structure and optical properties, we found that the theoretical transmittance of both compounds reaches 90% above 198 nm in the UV region. The bulk modulus and shear modulus of Ca3 Al2 Si3 O12 were calculated to be 181.41 and 115.84 GPa, respectively. The anisotropy in elastic properties along different crystallographic direction were found greater in Ca3 Al2 Si3 O12 than that in Mg3 Al2 Si3 O12 . The distinct dodecahedral coordinated Ca and Mg in the crystal structures result in the maximum Young's modulus existing in different direction, which is along [1 0 0] direction for Ca3 Al2 Si3 O12 but [1 1 1] direction for Mg3 Al2 Si3 O12 . Our theoretical investigations provided a basic understanding on the materials design of Ca3 Al2 Si3 O12 and Mg3 Al2 Si3 O12 .